Validation of the Use of Historical Events to Estimate the Age of Subjects Aged 65 Years and Over in Cotonou (Benin) - PARAÏSO, NOEL MOUSSILIOU; Houinato, Dismand; Guerchet, M.; AGUEH, VICTOIRE DAMIENNE AGOSSI; Nubukpo, Philippe; Preux, Pierre-Marie; Marin, B. (My University, 2010)
Background: Our aim was to validate the use of historical events as tools for estimating the age of people ≧65 years in Cotonou (Benin). Methods: The survey was conducted in Cotonou, the
Keywords: Estimate; Age; Cotonou